Effects of two methods of teaching badminton strokes on skill performance of children (2014)
This study investigated effects of two teaching styles on leaching badminton strokes on skill performance of children ages 8-11 years. A sample of 120 boys was randomly selected from a population of 310 volunteers in a private school in Ikoyi. Lagos State. Nigeria. Forty children each from this group were then randomly assigned to form two treatment groups and one control group who participated in the study using three teachers and three different styles. The teaching styles: command/practice. reciprocal and guided discover) were selected from spectrum. An experimental pre-test- post-test-control group design was employed in which the effects of the two treatments were examined under laboratory-like conditions. The teaching behaviours were measured using a computer-coding system devised for Ames's guidelines on how to create a mastery climate with the significant level at p<0.05. The two experimental groups were subjected to the treatment while the control group was exposed to placebo. Results revealed that the treatments groups with repeated measures on the trials factor yielded a significant main effect on the entry behaviour F (2.117) = 190.28. P.<0.05 for overhead dear and within the treatment groups, pre-to-mid-test differences were all found to be significant P<0.05. (6.26. 7.84) for underarm stroke and (0.76. 8.87) for overhead clear. Practice style proved to be an effective instructional strategy (pre M = 6.70, mid M = 9.43. post M = 15.98) for Underarm stroke and (pre M = 6.38. mid M = 8.35. post M = 17.20) for overhead clear respectively as this treatment group showed considerable progress from the pre-test to post-test. These results showed that the reciprocal and the practice styles are effective in enhancing pupils' performance and learning development in primary school physical education.